Revitalisasi Kain Tenun Baduy Melalui Adibusana: Peran Inovasi Dalam Melestarikan Warisan Budaya - Noor, Farzana Amatul (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
Baduy, as one of the tribes in Indonesia, has a tradition of woven fabric that is rich in cultural and aesthetic values. Combining traditional wisdom with modern fashion trends is expected to strengthen Indonesia’s cultural identity in the fashion world. The main purpose of this article is to explore and analyse the potential for innovation in the development of Baduy woven fabric as a ready-to-wear or couture material. This article aims to identify the opportunities and challenges in integrating local wisdom into the modern fashion industry, as well as provide a foundation for further developments in this field. The writing of this article is based on a literature study that involves searching for literature related to the history, manufacturing techniques, and meanings of Baduy woven fabrics. In addition, the literature study also includes literature on global fashion trends and the concept of haute couture. Data and information from reliable sources will be used to detail the innovative potential of Baduy woven fabric in the context of ready-to-wear, as well as discuss its impact on cultural preservation and the development of the fashion industry in Indonesia.